Pharmacokinetics of delta-9-tetrahydrocannabinol following acute cannabis smoke exposure in mice; effects of sex, age, and strain - Gazarov, Emely A.; Zequeira, Sabrina; Senetra, Alexandria S.; Howard, John; Sharma, Abhisheak; McCurdy, Christopher R.; Lewis, Jada; Bizon, Jennifer L.; Setlow, Barry (Frontiers in Pharmacology, 2023)
Increased use of cannabis and cannabinoids for recreational and medical purposes has led to a growth in research on their effects in animal models. The majority of this work has employed cannabinoid injections; however, smoking remains the most common route of cannabis consumption. To better model real-world cannabis use, we exposed mice to cannabis smoke to establish the pharmacokinetics of Δ9THC and its metabolites in plasma and brain. To determine the time course of Δ9THC and two major metabolites [11-hydroxy-delta-9-tetrahydrocannabinol (11-OH-THC) and 11-nor-9-carboxy-delta-9-tetrahydrocannabinol (11-COOH-THC)], male and female C57BL/6J mice were exposed to smoke from sequentially burning 5 cannabis cigarettes. Following smoke exposure, trunk blood and brains were collected at 6 time points (10 to 240 minutes). Plasma and brain homogenates were analyzed for Δ9THC and metabolites using a validated ultraperformance liquid chromatography-tandem mass spectrometry method. To assess effects of age, sex, and mouse strain, we exposed mice of four strains (C57BL/6J, FVB, Swiss Webster, and 129S6/SvEv, aged 4-24 months) to cannabis using the same smoke regimen. Samples were collected 10 and 40 min following exposure. Lastly, to assess effects of dose, C57BL/6J mice were exposed to smoke from burning 3 or 5 cannabis cigarettes, with samples collected 40 min following exposure. The pharmacokinetic study revealed that maximum plasma Δ9THC concentrations (Cmax) were achieved at 10 and 40 min for males and females, respectively, while Cmax for brain Δ9THC was observed at 20 and 40 min for males and females, respectively. There were no age or strain differences in plasma Δ9THC concentrations at 10 or 40 min; however, 129S6/SvEv mice had significantly higher brain Δ9THC concentrations than FVB mice. Additionally, 3 cigarettes produced significantly lower plasma 11-COOH-THC concentrations compared to 5 cigarettes, although dose differences were not evident in plasma or brain concentrations of Δ9THC or 11-OH-THC. Across all experiments, females had higher levels of 11-COOH-THC in plasma compared to males. The results reveal robust sex differences in Δ9THC pharmacokinetics, and lay the groundwork for future studies using mice to model the pharmacodynamics of smoked cannabis.